EP 37. Impedance changes occur during threshold measurements in subthalamic nucleus (STN) deep brain stimulation patients. Issue 9 (September 2016) - Volkmann, J.; Reich, M.; Kirsch, A.-D.; Timmermann, L.; Barbe, M.T.; Kühn, A.; van Riesen, C.; Whone, A.; Bigfoot, J.; Mooney, L.; Schnitzler, A.; Jun Groiss, S.; et al.
Abstract : Background: In previous work (Carcieri et al.), we observed impedance changes during the measurement of efficacy and side effect thresholds in seven DBS patients. This study investigates a larger group of subjects with more frequent impedance measurements to better characterize the time course of the effect and tests whether electrode impedance varies during the measurement of efficacy and side effect thresholds in DBS patients. Methods: Twenty-four patients, implanted in the STN with a current-controlled DBS system (Boston Scientific Corporation) for at least 3 months, were stimulated on 4 different electrode combinations using one or two active electrodes and amplitude was adjusted to measure thresholds. At the beginning and end of threshold measurements, impedance was measured. Average stimulation duration was under 20 min, and amplitude was increased to 5 mA on average. Results: Analysis reveals that turning stimulation ON resulted in an immediate reduction in impedance for 41/48 active electrodes, with a maximum decrease of 27%. The inactive electrodes showed a mean impedance decrease of 1%. For the active electrodes, the minimum impedance decrease was 2.8%, and the overall average decrease was 13.1%. Conclusions: Deep brain stimulation in the normal range for measurement of thresholds may result in large and rapid impedance changes on the active electrodes. Impedance changes of this magnitude and time scale may have clinical relevance for some patients.